Odpowiedzi

Najlepsza Odpowiedź!
  • Roma
  • Community Manager
2010-02-05T00:49:43+01:00
B. (3 - 4x² + 5x) - (-3x + 5x² + 3) = 3 - 4x² + 5x + 3x - 5x² - 3 = - 9x² + 8x

c. 9y + 5 + (2y + 3x - y) - 10y = 9y + 5 + 2y + 3x - y - 10y = 3x + 5

d. (¼x² - 0,2y - 3) - (-⅕y + 0,25x² - 3) = ¼x² - ⅕y - 3 + ⅕y - ¼x² + 3 = 0

e. (4a² - 3ab - 0,2a) + (-14a² + 2ab + 0,1a) = 4a² - 3ab - 0,2a - 14a² + 2ab + 0,1a = -10a² - ab - 0,1a
2 5 2
2010-02-05T00:53:44+01:00
Wykonaj redukcję wyrazów podobnych
b. (3-4x[2] + 5x) - (-3x + 5x[2] +3)
c. 9y + 5 + (2y + 3x - y) - 10y
d.(1/4x[2] - 0,2y - 3) - (-1/5y + 0,25x[2] - 3)
e. (4a[2] - 3ab - 0,2a) + (-14a[2] + 2ab + 0,1a)


b)3-4x²+5x+3x-5x²+3
-4x²-5x²+5x+3x+3-3
-9x²+8x

c)9y+5+2y+3x-y-10y
9y+2y-y-10y+5+3x
5+3x

d)1/4x[2] - 0,2y - 3) - (-1/5y + 0,25x[2] - 3)
1/4 x²-0,2y-3 +1/5 y -0,25x²+3
0,25x²-0,25x² -0,2y+0,2y +3 -3 =0


e)4a²-3ab-0,2a -14a² +2ab+0,1a
4a²-14a²-3ab+2ab-0,2a+0,1a
-10a²-ab-0,1a